Association between physical function and onset of coronary heart disease in a cohort of community-dwelling older populations: The SONIC study. (July 2021) - Klinpudtan, Nonglak; Kabayama, Mai; Godai, Kayo; Gondo, Yasuyuki; Masui, Yukie; Akagi, Yuya; Srithumsuk, Werayuth; Kiyoshige, Eri; Sugimoto, Ken; Akasaka, Hiroshi; Takami, Yoichi; Takeya, Yasushi; et al.
Highlights: Slow walking in older adults showed a higher risk of coronary heart disease (CHD). Walking speed can be surrogate marker to predict CHD in older adults. Improving the walking speed would lower the CHD risk in older populations. Abstract: Background: Physical function is a strong predictor of the adverse outcomes of cardiovascular disease in older populations. However, studies of healthy older people on the prevention of coronary heart disease (CHD) are very limited. Objectives: We prospectively examined the association of walking speed and handgrip strength with CHD in the community-dwelling older populations. Methods: The study cohort in Japan included 1272 older people free from heart disease at the baseline. Physical function was identified based on walking speed and handgrip strength assessment at the survey site. Any new case of CHD was identified based on a self-reported doctor's diagnosis. Cox-proportion hazard models were adjusted for covariate factors to examine the CHD risk. Results: During the 7-year follow-up, 45 new cases of CHD (25 men and 20 women) were documented. Slow walking speed was strongly associated with CHD risk after adjusting for all confounding factors in the total participants and women (hazard ratio (HR)= 2.53, 95%confidence interval (CI), 1.20-5.33, p=0.015, and HR= 4.78, 95% CI, 1.07-21.35, p=0.040, respectively), but not in men. Weak grip strength was associated with CHD after age-adjustment (HR= 2.45, 95%CI, 1.03-5.81, p=0.043) only in men. However, after additional multivariate adjustment, the associations were getting weaker.